2004
DOI: 10.1038/nrc1501
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the cytoskeleton: an oncogenic function for cdk inhibitors?

Abstract: Cyclin-dependent kinase inhibitors (CKIs) are well known inhibitors of cell proliferation. Their activity is disrupted in many tumour types. Recent studies show that some of these proteins have interesting alternative functions, acting in the cytoplasm to regulate Rho signalling and thereby controlling cytoskeletal organization and cell migration. The upregulation of CKIs in the cytoplasm of many cancer cells indicates that although loss of nuclear CKIs is important for cancer cell proliferation, gain of cytop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
167
0
9

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(180 citation statements)
references
References 59 publications
4
167
0
9
Order By: Relevance
“…This raises the possibility that the role of p21 in tumorigenesis is influenced by its subcellular localization. Consequently, whereas nuclear p21 inhibits CDK activity and halts cell-cycle progression, cytoplasmic p21 has an opposite function, contributing to oncogenesis 90 . Cytoplasmic p21 can interact with, and thereby inactivate, multiple pro-apoptotic proteins such as SAPK (also known as JNK) 91 , pro-caspase 3 (REF.…”
Section: Is P21 Required For Oncogenic Transformation?mentioning
confidence: 99%
“…This raises the possibility that the role of p21 in tumorigenesis is influenced by its subcellular localization. Consequently, whereas nuclear p21 inhibits CDK activity and halts cell-cycle progression, cytoplasmic p21 has an opposite function, contributing to oncogenesis 90 . Cytoplasmic p21 can interact with, and thereby inactivate, multiple pro-apoptotic proteins such as SAPK (also known as JNK) 91 , pro-caspase 3 (REF.…”
Section: Is P21 Required For Oncogenic Transformation?mentioning
confidence: 99%
“…It is a cyclin-dependent kinase (Cdk) inhibitor (CKI) that inhibits a variety of cyclin/ Cdk complexes including cyclin D/Cdk4/6 and cyclin E/Cdk2. The p27 mediates arrest at G1 of the cell cycle in response to transforming growth factor ÎČ (TGF-ÎČ), contact inhibition, or serum deprivation in epithelial cell lines [12][13][14]. Mice deficient for p27 display increased body size and enlarged organs, which contain more cells than wild type [15][16][17].…”
Section: The Role Of Cell Proliferation In Size Controlmentioning
confidence: 99%
“…Indeed, some studies have indicated that p27 levels in tumors do not always correlate with proliferative index, and increasing evidence points to the importance of the subcellular localization of p27 in the control of its function, with cytoplasmic localization being a negative prognostic factor in certain instances (Singh et al 1998;Nakasu et al 1999;Saez et al 1999;Sanchez-Beato et al 1999;Slingerland and Pagano 2000;Philipp-Staheli et al 2001;Kouvaraki et al 2002;Liang et al 2002;Besson et al 2004a;Rosen et al 2005;Qi et al 2006). This possibility is supported by in vivo studies: p27 +/− mice are more susceptible to tumor development than p27 −/− animals in mammary and prostate tumor models, suggesting an active contribution of the remaining p27 allele (Muraoka et al 2002;Gao et al 2004).…”
mentioning
confidence: 99%